The Old Testament prophets - Heaton, Eric William, 1920 (Harmondsworth, UK Penguin, 1961)
Includes bibliographical references and index.
First edition published 1958 , however this book is a completely revised and largley rewritten edition of "His servants the prophets" (SCM, 1949).
Keywords: Bible. O.T. Prophetic books -- criticism, interpretation, etc